Extracorporeal cardiopulmonary resuscitation versus standard treatment for refractory out-of-hospital cardiac arrest: a Bayesian meta-analysis - Heuts, Samuel; Ubben, Johannes F H; Kawczynski, Michal J; Gabrio, Andrea; Suverein, Martje M; Delnoij, Thijs S R; Kavalkova, Petra; Rob, Daniel; Komárek, Arnošt; van der Horst, Iwan C C; Maessen, Jos G; Yannopoulos, Demetris; et al. (Critical care (London, England), 2024)
BACKGROUND: The outcomes of several randomized trials on extracorporeal cardiopulmonary resuscitation (ECPR) in patients with refractory out-of-hospital cardiac arrest were examined using frequentist methods, resulting in a dichotomous interpretation of results based on p-values rather than in the probability of clinically relevant treatment effects. To determine such a probability of a clinically relevant ECPR-based treatment effect on neurological outcomes, the authors of these trials performed a Bayesian meta-analysis of the totality of randomized ECPR evidence. METHODS: A systematic search was applied to three electronic databases. Randomized trials that compared ECPR-based treatment with conventional CPR for refractory out-of-hospital cardiac arrest were included. The study was preregistered in INPLASY (INPLASY2023120060). The primary Bayesian hierarchical meta-analysis estimated the difference in 6-month neurologically favorable survival in patients with all rhythms, and a secondary analysis assessed this difference in patients with shockable rhythms (Bayesian hierarchical random-effects model). Primary Bayesian analyses were performed under vague priors. Outcomes were formulated as estimated median relative risks, mean absolute risk differences, and numbers needed to treat with corresponding 95% credible intervals (CrIs). The posterior probabilities of various clinically relevant absolute risk difference thresholds were estimated. RESULTS: Three randomized trials were included in the analysis (ECPR, n = 209 patients; conventional CPR, n = 211 patients). The estimated median relative risk of ECPR for 6-month neurologically favorable survival was 1.47 (95%CrI 0.73-3.32) with a mean absolute risk difference of 8.7% (- 5.0; 42.7%) in patients with all rhythms, and the median relative risk was 1.54 (95%CrI 0.79-3.71) with a mean absolute risk difference of 10.8% (95%CrI - 4.2; 73.9%) in patients with shockable rhythms. The posterior probabilities of an absolute risk difference > 0% and > 5% were 91.0% and 71.1% in patients with all rhythms and 92.4% and 75.8% in patients with shockable rhythms, respectively. CONCLUSION: The current Bayesian meta-analysis found a 71.1% and 75.8% posterior probability of a clinically relevant ECPR-based treatment effect on 6-month neurologically favorable survival in patients with all rhythms and shockable rhythms. These results must be interpreted within the context of the reported credible intervals and varying designs of the randomized trials. REGISTRATION: INPLASY (INPLASY2023120060, December 14th, 2023, https://doi.org/10.37766/inplasy2023.12.0060 ).
Keywords: výsledek terapie; Cardiopulmonary Resuscitation; kardiopulmonální resuscitace; Out-of-Hospital Cardiac Arrest; Treatment Outcome; Randomized Controlled Trials as Topic; Humans; Extracorporeal Membrane Oxygenation; randomizované kontrolované studie jako téma; zástava srdce mimo nemocnici; Bayes Theorem; Bayesova věta; lidé; mimotělní membránová oxygenace